Lingkungan Kerja dan Locus of Control Sebagai Pemoderasi Pengaruh Penggunaan Teknologi Informasi Pada Keandalan Pelaporan Keuangan Pemerintah Daerah - Andayani, Rai Dwi; Widanaputra, A.A.G.P; Astika, Ida Bagus Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
This study is motivated by the increasing use of technology, it is expected that financial reporting will be more reliable, it is related to the increasing demand of the society towards good governance government, has encouraged the central government and local government to implement public accountability. This study aims to obtain empirical evidence that the work environment and internal locus of control able to strengthen the influence of the use of information technology on the reliability of local government financial reporting.Data of this research were collected through survey method with questionnaire technique and analyzed by moderation regression analysis (MRA / Moderated Regression Analysis). The sample was taken using a saturated sample with an individual's analysis unit at each of the Regional Device Organization (OPD).The results of the analysis show that the work environment and internal locus of control strengthen the influence of the use of information technology on the reliability of local government financial reporting. These empirical results reinforce the theory of Technology Acceptance Model (TAM) and attribution theory as a foundation for studying and understanding user behavior of information technology users either internally or externally caused behavior.